Anti-tumor T-cell homeostatic activation is uncoupled from homeostatic inhibition by checkpoint blockade - Marshall, Netonia (Cancer Discov, 2019)
T-cell transfer into lymphodepleted recipients induces homeostatic activation and potentiates anti-tumor efficacy. In contrast to canonical TCR-induced activation, homeostatic activation yields a distinct phenotype and memory state whose regulatory mechanisms are poorly understood. Here, we show in patients and murine models that, following transfer into lymphodepleted bone marrow transplant (BMT) recipients, CD8(+) T-cells undergo activation but also simultaneous homeostatic inhibition manifest in upregulation of immune checkpoint molecules and functional suppression. T-cell transferred into BMT recipients were protected from homeostatic inhibition by PD1/CTLA4 dual checkpoint blockade (dCB). This combination of dCB and BMT–’immunotransplant’– increased T-cell homeostatic activation and anti-tumor T-cell responses by an order of magnitude. Like homeostatic activation, homeostatic inhibition is IL-7/IL-15-dependent, revealing mechanistic coupling of these two processes. Marked similarity in ex vivo modulation of post-BMT T-cell in mice and patients is promising for the clinical translation of immunotransplant (NCT03305445) and for addressing homeostatic inhibition in T-cell therapies.